The closure of Wyoming’s Program of All-Inclusive Care for the Elderly (PACE): Qualitative analysis of the impact on social isolation and loneliness - Dabrowski, Barbara S.; McKibbin, Christine L.; O'Barr, Gregory W.; Punke, Elizabeth L.; Teply, Abby L.; Richardson, Kathryn A.; Carrico, Catherine P. (Frontiers in Public Health, 2024)
IntroductionSocial isolation and loneliness are global public health concerns experienced among older adults which are commonly associated with negative physical, psychological, and social outcomes. The healthcare system has an opportunity to identify and address social isolation and loneliness in older adults. The Program of All-Inclusive Care for the Elderly (PACE) was developed to serve comprehensive social needs along with medical and behavioral needs of older adults who qualify for long-term care while still living in the community. In 2021, due to state budget reductions, Wyoming’s only PACE program (WY PACE) closed, resulting in the discharge of all participants and loss of social engagement opportunities provided by this program. The objectives of this evaluation were to (1) examine the impact of the WY PACE closure on isolation and loneliness, (2) identify how older adults adapted to the loss of services addressing isolation and loneliness, and (3) identify needs for future interventions to address isolation among clients who experienced loss of supportive programs.MethodsA mixed-methods design was used to facilitate understanding of qualitative findings while also conducting quantitative analyses to provide context for qualitative responses. Participants included 17 individuals who were either former PACE participants or their caregivers. Participants (n = 12; M = 74 years old) were predominantly non-Hispanic White (n = 8, 66%) and cisgender female (n = 7, 58%). Caregivers of participants (n = 5; M = 63 years old) were predominantly Hispanic, Latino, or of Spanish origin (n = 3, 60%) and cisgender female (n = 4, 80%).ResultsA mixed-methods design was used to facilitate understanding of qualitative findings while also conducting quantitative analyses to provide context for qualitative responses. Participants included 17 individuals who were either former PACE participants or their caregivers. Participants (n = 12; M = 74 years old) were predominantly non-Hispanic White (n = 8, 66%) and cisgender female (n = 7, 58%). Caregivers of participants (n = 5; M = 63 years old) were predominantly Hispanic, Latino, or of Spanish origin (n = 3, 60%) and cisgender female (n = 4, 80%).DiscussionThis evaluation provided preliminary insight into the impacts of the loss of programs like WY PACE on social isolation and loneliness. Creative solutions to maintain social engagement of this vulnerable population are needed.